The digital MIQE Guidelines update: minimum information for publication of quantitative digital PCR experiments for 2020 - Huggett, Jim; Untergasser, Andreas (Clinical chemistry, 2020)
Abstract. Digital PCR (dPCR) has developed considerably since the publication of the Minimum Information for Publication of Digital PCR Experiments (dMIQE) gui